How to bridge the nurse innovation-diffusion gap? An in-depth case study of Create4Care - Coen Rigtering; Lara J. Spaans; Jeroen P. J. de Jong (Frontiers Media S.A., 2023)
IntroductionNurses frequently innovate in response to operational failures, regulations, procedures, and/or other workflow barriers that prevent them from delivering high-quality patient care. Unfortunately, most nurse innovations do not diffuse to a broader audience, depriving other nurses from taking advantage of solutions that have already been developed elsewhere. This under-diffusion is problematic from a societal and welfare point of view. The goal of this paper is to understand how diffusion shortage of nurse innovations can be reduced.MethodsWe develop a qualitative case study of a medical makerspace at the largest academic hospital in the Netherlands. This medical makerspace reported unusually high rates of nurse innovation diffusion. Our data collection includes on-site observations, archival data, secondary data, and fifteen in-depth interviews with key informants. Qualitative coding procedures and a combination of deductive and inductive reasoning are used to analyze the data.ResultsOur data show that personal, organizational, regulatory, and market barriers prevent nurses from further developing and diffusion their innovations in an anticipatory manner. That is, because nurses expect that transforming an initial solution into an innovation that can be shared with others will be too time consuming and difficult they do not proceed with the further development. The medical makerspace that we investigated adequately addresses this problem by developing an innovation ecosystem that largely takes over the innovation and diffusion process.DiscussionWe provide a concrete example of how a medical makerspace, and innovation support systems in a broader sense, can be designed to more adequately address the nurse innovation-diffusion gap. The two main elements of the practical solution that we identified are: (1) Support systems should facilitate that others may lead the development and diffusion of innovations and (2) The support system should promote that actors integrate their functional specializations within an innovation ecosystem. We make two theoretical contributions. First, we contribute to understanding barriers in the nurse innovation-diffusion process from a psychological point. Second, we identified that an ecosystem perspective is beneficial to develop innovation support systems in which diffusion occurs more often.